HEMATOGRAM ANJING LOKAL (Canis familiaris) YANG DIINFEKSI Microsporum canis - , FIFI HINDHISCANINGRUM; , Dr. drh. Soedarmanto Indarjulianto, ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Microsporum canis is the major agent of dermatophytosis in dogs. Dermatophytosis may cause discomfort of dogs, such as pruritus, itchi, and resulted in lost appetite. Lost appetite may result in blood feature change. Therefore, this study is crudicted to evaluate the profile of erythrocyte, hemoglobin (Hb), packed cell volume (PCV), mean corpuscullar volume (MCV), mean corpuscullar hemoglobin (MCH), and also mean corpuscullar hemoglobin concentration (MCHC) in dog infected Microsporum canis. Six female and male dogs with the aged of 6-8 months were used in this study. Dogs who infected with M. canis by scratching sublumbal skin with the osa. Blood sample were take pre-infection and 14 days post-infection. Result of these study show that there was not significant difference value in erythrocytes, Hb, PCV, MCV, MCH, and MCHC levels before and after infection (p> 0.05). Infection of M. canis does not cause changes in the number of erythrocytes, hemoglobin concentration, the value of PCV, MCV, MCH, and MCHC of normal limits.